2006
DOI: 10.1097/00000542-200611000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Remifentanil-induced Analgesia and Postinfusion Hyperalgesia by Parecoxib in Humans

Abstract: The results confirm clinically relevant interaction of mu opioids and prostaglandins in humans. Adequate timing seems to be of particular importance for the antihyperalgesic effect of cyclooxygenase-2 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(44 citation statements)
references
References 45 publications
0
44
0
Order By: Relevance
“…6,39,60,68,73,80,112,133,134 Along with opioid, neurokinin 1, and toll-like receptor 4 antagonists, NSAIDS and gabapentinoids have been found to reduce neuroinflammation and mitigate OIH and/or WIH in some 1,5,14,18,34,45,46,61,70,83,85,94,100,121,127,135,137 but not all 50 circumstances. In our study, a subset of participants named NSAIDs most frequently and gabapentinoids third for relieving WISP, supporting a possible neuroinflammatory component.…”
Section: Discussionmentioning
confidence: 99%
“…6,39,60,68,73,80,112,133,134 Along with opioid, neurokinin 1, and toll-like receptor 4 antagonists, NSAIDS and gabapentinoids have been found to reduce neuroinflammation and mitigate OIH and/or WIH in some 1,5,14,18,34,45,46,61,70,83,85,94,100,121,127,135,137 but not all 50 circumstances. In our study, a subset of participants named NSAIDs most frequently and gabapentinoids third for relieving WISP, supporting a possible neuroinflammatory component.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors showed that the OIH can develop differently for different types of pain such as transdermal electrical stimulation (Angst et al, 2003; Hood et al, 2003; Koppert et al, 2003a,b; Troster et al, 2006), cold pressor pain (Compton et al, 2003, 2004), and pressure-evoked pain (Luginbuhl et al, 2003). Transdermal electrical stimulation used for inducing mechanical hyperalgesia on an experimental skin lesion rendered hyperalgesia in human volunteers.…”
Section: General Consensus Of Aot and Oihmentioning
confidence: 99%
“…Transdermal electrical stimulation used for inducing mechanical hyperalgesia on an experimental skin lesion rendered hyperalgesia in human volunteers. These investigators suggested that 30–90 min of remifentanil exposure significantly enlarge the skin area with pre-existing mechanical hyperalgesia by transdermal electrical stimulation with direct relation of the infusion duration and the opioid dose (Angst et al, 2003; Hood et al, 2003; Koppert et al, 2003a,b; Troster et al, 2006). This hyperalgesia was sustained up to 4 h after stopping infusion (Hood et al, 2003).…”
Section: General Consensus Of Aot and Oihmentioning
confidence: 99%
“…Although this phenomena has been observed in preclinical investigations [5, 38, 40] and in experimental pain studies involving humans [1, 36, 54], the potential hyperalgesic effects of long-term opioid use on pain perception in adults with chronic pain have not been widely reported [21]. Thus, an important knowledge gap exists regarding the occurrence of OIH in samples of community-dwelling adults with chronic pain receiving long-term opioid therapy.…”
Section: Introductionmentioning
confidence: 99%